Activity Volcano Plots for the Oxygen Reduction Reaction Using fen4 Complexes: From Reported Experimental Data to the Electrochemical Meaning - Ureta-Zanartu, M; Zagal-Moya, J; Zagal-Moya, J; Tasca-Gottardo, F; Tasca-Gottardo, F; Zúñiga-Loyola, C; Zúñiga-Loyola, C (Elsevier B.V., 2022)
Electrochemistry and electrochemical experiments are powerful tools for obtaining information about the thermodynamics and kinetics of electrochemical reactions. In electrocatalysis, these two parameters are often framed together to improve the understanding of the interactions of a catalyst and a reactant. Generally, “volcano-type” correlations are composed to compare similar catalysts. In this type of correlation, kinetic versus thermodynamic parameters are juxtapose to identify the most active catalyst positioned at the top of the volcano trend. In this work, we delve into the obtaining of this type of correlations to clarify the significance and utility. In particular, the study of the oxygen reduction reaction (ORR) has been selected due to its importance in energy conversion devices such as fuel cells and metal-air batteries. © 2021 Elsevier B.V.